Persepsi wisatawan pada destinasi alam dan geowisata di Jawa Timur - Virgian Wahyu Saputra; M. Saiful Anam; M. Alief Afriliansyah (CV. ITTC INDONESIA, 2025)
This study aims to explore tourists' perceptions of nature based and geotourism destinations in three regencies of East Java: Nganjuk with Sedudo Waterfall, Mojokerto with Sarah Klopo, and Sidoarjo, known for the Lapindo Mud. A phenomenological method was employed to explore the personal experiences of tourists through direct observation and interviews, allowing for a deeper understanding of the meanings and impressions felt by visitors. The findings reveal that each tourism site has its own distinctive features and attractions that create positive perceptions among tourists. Sedudo Waterfall is renowned for its stunning natural beauty and preserved cultural values, offering an experience that is both recreational and educational. Sarah Klopo combines natural adventure with historical significance, providing a unique and profound experience. The Lapindo Mud in Sidoarjo serves as a reminder of a past natural disaster while also functioning as an educational site that underscores the importance of environmental management and disaster risk reduction.